A complexidade dos sistemas de assentamentos ameríndios no Planalto Ocidental Paulista vistos a partir da arqueologia: a contribuição do LAG/MAR - Neide Barrocá Faccio (Confins)
The Western Plateau of São Paulo State was once densely occupied by indigenous peoples. It is presented, here, the archaeological data of the indigenous occupations surveyed in the Western Plateau of São Paulo State, by the LAG (Laboratory of Guarani Archeology and Landscape Studies) and MAR (Museum of Regional Archeology) of FCT / UNESP (Faculty of Science and Technology / Paulista State University). In the Western Plateau of São Paulo State we find the Guarani and / or Tupi ethnic groups, Kaingang and Kayapó Indians. The objective is to clarify the material culture, from the characterization of the objects, the form of the dwellings and the physical environment of these occupations, from which, although in an initial way, it´s possible to know, at least in part, the characteristics of these indigenous groups.